2021
DOI: 10.4081/gh.2021.954
|View full text |Cite
|
Sign up to set email alerts
|

Role of transport network accessibility in the spread of COVID-19 - a case study in Savar Upazila, Bangladesh

Abstract: The aim of this research was to test the hypothesis that people in a typical high-transport zone are particularly vulnerable with respect to transmission of coronavirus disease 2019 (COVID-19), a new contagious disease that has rapidly developed into a highrisk global problem. A case study was carried out in Savar Upazila, a sub-district of the capital city Dhaka in Bangladesh, which is traversed by a prominent national highway (Dhaka- Aricha-N5) that also passes the concentric industrial export processing zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A method of visualizing the spatial and chronological aspects of the spread of this virus based on geographical information systems (GIS) was recently reported [ 51 ], and a case study in Bangladesh found COVID-19 to be strongly associated with the reach and mechanism of transport networks [ 52 ]. Gephi graphs based on qualitative data from newspaper reports and prepared layouts varying from macro to micro scales show that this approach can enrich traditional GIS approaches, thereby assisting mobility planners and policymakers [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…A method of visualizing the spatial and chronological aspects of the spread of this virus based on geographical information systems (GIS) was recently reported [ 51 ], and a case study in Bangladesh found COVID-19 to be strongly associated with the reach and mechanism of transport networks [ 52 ]. Gephi graphs based on qualitative data from newspaper reports and prepared layouts varying from macro to micro scales show that this approach can enrich traditional GIS approaches, thereby assisting mobility planners and policymakers [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“… Aragão et al (2022) find a correlation between humidity, temperature, and air quality with the number of COVID-19 deaths. Some authors model the effect of mobility restrictions on the decrease in the number of infections ( Bian et al, 2021 , Lima et al, 2021 ) and the crowding of people in stations ( Hamidi and Hamidi, 2021 , Mahmud et al, 2021 , Scott et al, 2021 ). Hamidi & Hamidi (2021) note that there is no evidence that subway ridership is related to the COVID-19 infection rates, and show that racial and socioeconomic compositions are identified among the most significant predictors of spatial variation of the spread of the virus.…”
Section: Transportation Policies and Mitigations Strategiesmentioning
confidence: 99%
“…The global outbreak of coronavirus disease 2029 in early 2020 had a detrimental effect on public health throughout the world and provoked lockdowns in a number of countries, including China, Spain, India, Iran, United Kingdom, Italy, France, Germany, Brazil, Russia and the United States (Giuliani et al, 2020;D'Angelo et al, 2021;Mahmud et al, 2021;Mohammad Ebrahimi et al, 2021;Nikparvar et al, 2021;Valente and Laurini, 2021).…”
Section: Introductionmentioning
confidence: 99%